Comparative study on natural insect repellent properties of Euphorbia hirta and Plectranthus amboinicus - Hazri, Hanis Nur Nabilah; Muhammad, Arbanah; Rozali Annuar, Nur Hazirah; Abdul Halim, Siti Rahika (Universiti Teknologi MARA Shah Alam, 2025)
Growing concern over the health and environmental risks of synthetic repellents like DEET and permethrin has spurred interest in natural, plant-based alternatives. Although many plants have long been used in Malaysia for traditional medicine and pest control, scientific evidence of their repellent potential remains limited. Therefore, this study aims to (1) evaluate the insect repellent efficiency of Euphorbia hirta (E. hirta) and Plectranthus amboinicus (P. amboinicus) against hematophagous insects, ants and (2) characterise the bioactive compounds responsible for their repellent properties. The active compounds of phenolic, terpenoids, thymol, and carvacrol from the plants were extracted using ethanol via Soxhlet extraction and concentrated using a rotary evaporator. Repellence tests were conducted at a 10% concentration, with formulations prepared based on terpenoid-to-phenolic ratios of 3:2, 1:1, and 2:3. Results revealed that P. amboinicus contained high levels of thymol (41.9%) and carvacrol (28.5%), while E. hirta showed notable amounts of quercetin (4.5%) and kaempferol (3.2%). P. amboinicus exhibited stronger repellence against ants at higher terpenoid-tophenolic ratio of 3:2, whereas E. hirta demonstrated effective repellence even at lower ratio of 1:1, with minimal ant attraction. Overall, both plants showed promising insect repellent activity, with P. amboinicus being more effective at higher concentrations. These findings emphasise the attractiveness of plant-based repellents as sustainable pest control solutions, reducing reliance on synthetic chemicals and promoting ecofriendly practice.